Corporate Performance Measurement in the E-Commerce - Csáki-Darabos, Rita; Csáki-Darabos, Rita (International Journal of Engineering and Management Sciences, 2017)
Performance of the domestic online commerce showed a dynamic increase in recent years and, based on the expected forecasts, this trend will be realized in the future as well. In Hungary, the number of electronic commerce undertakings is estimated to be within a range of between 5 000 and 6 000 pieces and this number is steadily increasing. Today, the opportunities offered by the internet play an increasingly significant role in every segment of the economy. In the increasing market competition, it is no longer sufficient to serve the local population. Driver of the internet commerce is a marketing activity therefore the performance measurement is a priority. The excellent result and success essentially and principally depend on the performance, in addition to luck. Performance is understood as the measurable results or, in the broad sense, the successful efforts which are made to achieve the organizational objectives. The performance measurement is a measurement process of the efficiency and economy of an activity. Its aim is to support the decisions and actions related to the operation of the undertaking. The performance measurement is not only a decision support tool but also an element influencing every level of the decision-making system; it has an effect on the actions of stakeholders. Its danger and importance are simultaneously the fact that its improper operation (application of incorrect yardstick) can result in a functioning contrary to the corporate objectives. My aim is to survey the corporate performance measurement practice, to assess the connection between the financial and operational performance as well as to analyse the connection between the performance measurement practice and the performance achieved.